Effects of Treatment With Hypnotics on Reduced Sleep Duration and Behavior Abnormalities in a Mouse Model of Fragile X Syndrome - Saré, Rachel Michelle; Lemons, Abigail; Smith, Carolyn Beebe (Frontiers in Neuroscience, 2022)
Many patients with fragile X syndrome (FXS) have sleep disturbances, and Fmr1 knockout (KO) mice (a model of FXS) have reduced sleep duration compared to wild type (WT). Sleep is important for brain development, and chronic sleep restriction during development has long-lasting behavioral effects in WT mice. We hypothesized that the sleep abnormalities in FXS may contribute to behavioral impairments and that increasing sleep duration might improve behavior. We treated adult male Fmr1 KO and WT mice subacutely with three different classes of hypnotics (DORA-22, ramelteon, and zolpidem) and caffeine, a methylxanthine stimulant, and we tested the effects of treatments on sleep duration and behavior. Behavior tests included activity response to a novel environment, anxiety-like behavior, and social behavior. As expected, all hypnotics increased, and caffeine decreased sleep duration in the circadian phase in which drugs were administered. Caffeine and DORA-22 treatment significantly reduced activity in the open field regardless of genotype. Other effects were not as apparent possibly due to the short duration of treatment.